(untitled) (Docentes 2.0 Journal, 2024)
The digital contemporaneity of radio, written press, and television has transitioned towards digital platforms in response to the growing use of the Internet and digital technology. This migration aimed to capture the attention of millennials and society, who increasingly consume information through the web and social networks; effectively reaching the public in science and technology becomes crucial. The research involved science journalists and academics using a qualitative approach with a case study design. Methodologically, bibliographic review, scientific content analysis techniques, and semi-structured interviews were integrated as essential instruments. In this scenario of constant change and growth of the Internet, with Web 3.0, the need to update educational digital tools to train professionals specialized in scientific communication stands out. Ideal in dynamic digital environments, these adaptations are essential to prepare future professionals to face the emerging challenges of the contemporary communication landscape of science and scientific dissemination.